Gymnasts' special quickness-force abilities and the indicators of jump from a springboard - Koperski, A.; Kochanowicz, A.; Slodkowski, C. (Baltic Journal of Health and Physical Activity, 2010)
Background: The aim of this research is to find a relation between one's special quickness-force abilities, recorded in laboratory conditions, and physical values, revealed during a gymnastic jump in a real sports contest.